Association between smoking and alcohol‐related behaviours: a time–series analysis of population trends in England. (6th July 2017) - Beard, Emma; West, Robert; Michie, Susan; Brown, Jamie
Abstract: Aims: This paper estimates how far monthly changes in prevalence of cigarette smoking, motivation to quit and attempts to stop smoking have been associated with changes in prevalence of high‐risk drinking, and motivation and attempts to reduce alcohol consumption in England. Design: Data were used from the Alcohol and Smoking Toolkit Studies between April 2014 and June 2016. These involve monthly household face‐to‐face surveys of representative samples of 1700 adults in England. Measurements: Autoregressive Integrated Moving Average with Exogeneous Input (ARIMAX) modelling was used to assess the association over time between monthly prevalence of (a) smoking and high‐risk drinking; (b) high motivation to quit smoking and high motivation to reduce alcohol consumption; and (c) attempts to quit smoking and attempts to reduce alcohol consumption. Findings: Mean smoking prevalence over the study period was 18.6% and high‐risk drinking prevalence was 13.0%. A decrease of 1% of the series mean smoking prevalence was associated with a reduction of 0.185% of the mean prevalence of high‐risk drinking 2 months later [95% confidence interval (CI) = 0.033 to 0.337, P = 0.017]. A statistically significant association was not found between prevalence of high motivation to quit smoking and high motivation to reduce alcohol consumption (β = 0.324, 95% CI = –0.371 to 1.019, P = 0.360) or prevalence of attempts to quit smoking and attempts to reduce alcohol consumption (β = −0.026, 95% CI = –1.348 to 1.296, P = 0.969). Conclusion: Between 2014 and 2016, monthly changes in prevalence of smoking in England were associated positively with prevalence of high‐risk drinking. There was no significant association between motivation to stop and motivation to reduce alcohol consumption, or attempts to quit smoking and attempts to reduce alcohol consumption.